Concurrent Helminthosis and Plastic-induced Rumen Impaction in a Kano Brown Doe (Capra hircus): Clinical Management and Pathology Findings - Kogi, A. C.; Oshadu, D. O.; Karaye, G. P.; Biallah, M. B.; Godwin, C. U.; Buba, D. N. (Direct Research Journal of Veterinary Medicine and Animal Science, 2026)
Background: The role of livestock is pivotal in the livelihoods of rural and sub-urban communities. Small ruminants contribute substantially to food security, household income, and economic sustainability in sub-Saharan Africa. However, productivity is severely constrained by gastrointestinal helminthosis and rumen impaction. Nematodes are common causes of gastrointestinal infection especially Haemonchus contortus while rumen impaction is as a result of nutritional deficiencies and poor management practices. Case Presentation: A One-Year-old Kano Brown doe weighing 15.9 kg was presented to the Veterinary Teaching Hospital University of Jos, Jos, with the complaint of malaise, lethargy, rough hair coat, vocalization, pale mucous membranes, ataxia, and a history of anorexia. Diagnosis: On physical examination, ticks were observed on the body while abdominal ballottement revealed presence of a palpable hard mass in the caudal third of the left abdominal region. Clinical examination revealed that vital parameters: temperature, pulse and respiratory rate were all within normal range. Laboratory investigations revealed a PCV of 27%, TWBC 2800, while faecal floatation technique showed presence of strongyle type eggs +++ and coccidia oocysts ++. Management/Treatment: At presentation, the animal was stabilized with Dextrose saline and lactated Ringers’ solution given intravenously. Dexamethasone was administered via the intramuscular route. The doe was scheduled for rumenotomy pending resuscitation. Outcome: Post-treatment monitoring showed that the doe was not improving, did not stabilize and eventually died. Pathology Findings: At post-mortem examination, a mass of plastic bag with trapped ingesta weighing 4.3 kg was recovered from the rumen. Further observation of the liver and kidneys revealed enlargement and congestion of the organs. Conclusion: Concurrent gastrointestinal helminthosis and plastic-induced rumen impaction is a major constraint to production performance of small ruminants in sub-Saharan Africa. This case report, though uncommon, highlights the severity and consequent economic impact of the condition on small ruminant holders. Helminthosis and foreign body rumen impaction have severe negative consequences on livestock production and reproduction, particularly in females. Efforts should be intensified to protect small ruminants especially goats and sheep from contaminated pastures and indiscriminate disposal of harmful and non-biodegradable materials in the environment, as well as discouraging the extensive system of management.